Health effects, environmental impacts, and photochemical degradation of selected surfactants in water - Sarah Hatfield Venhuis; Mehrab Mehrvar (International Journal of Photoenergy)
Surfactants are depended upon worldwide as cleaning agents. Their usage in such large quantities means that their waste and the potential for pollution are high. Many studies have been done over the last three decades encompassing treatment, alternatives to non-biodegradable surfactants, and the environmental impact. It has been found that although certain surfactants may not be directly toxic, when their concentrations are high in soil, they can act as agents to release toxic pollutants such as polychlorinated biphenyls (PCBs). The focus of this study is to review recent advances in the toxicology, the environmental fate, and the treatment of selected surfactants. In addition, photolytic and photocatalytic degradation of linear alkylbenzene sulfonate in water is presented.